Tree felling by beaver promotes regeneration in riparian woodlands whilst increasing resource availability for deer - Wilson, Kelsey A.; Law, Alan; Hester, Alison J.; Gaywood, Martin J.; Willby, Nigel J. (Forest ecology and management, 2024)
Interactions between species influence ecosystem functions and are sensitive to reintroductions. Our understanding of interactions between naturally co-occurring large herbivores, such as Eurasian beaver (Castor fiber) that are now re-establishing throughout their range, and well-established native ungulates, is limited, despite the potential implications for riparian woodlands. Observations in Scotland indicate that roe deer (Capreolus capreolus) readily exploit the regenerative secondary shoots produced after tree felling by beaver. Our study, based in eastern Scotland, investigates the role of beaver herbivory in riparian woodland regeneration and asks whether deer are attracted to this novel resource because it is either a) more readily available, b) nutritionally superior, or c) morphologically more appealing than accessible browse on unfelled (standing) trees. We firstly quantified the secondary shoots available to browsing deer at different heights on felled and standing birch (Betula spp.) trees in twenty riparian woodland plots across five well-established beaver territories (occupancy ten years). Shoots from birch and willow (Salix spp.) trees with contrasting levels and combinations of beaver and deer browsing were then analysed for nutritional content (nitrogen and carbon) and morphological characteristics (number of buds and lateral branches). We found that 62% of beaver-felled trees produced secondary shoots available to browsing deer. Compared to standing trees, regenerating beaver-felled trees had 18% more secondary shoots. These shoots were significantly higher in nitrogen content (+13%), but similar in carbon content and concentrated closer to the ground. Our results show that beaver herbivory can promote riparian woodland regeneration and heterogeneity by creating a mosaic of mature and multi-stemmed coppiced trees. The addition of a common, readily available, and nutritious resource through beaver browsing could, however, also enhance habitat quality for browsing deer, with the potential to affect deer distribution and feeding habits. •Tree felling by beaver promotes riparian woodland regeneration.•Among beaver-felled trees 62 % produced secondary shoots accessible to deer.•Beaver-felled trees yielded more shoots (+18 %) that were richer in nitrogen (+13 %).•Tree felling by beaver could influence deer feeding and distribution.•Beaver-deer interactions have implications for riparian woodland conservation.